Improving work–nonwork balance and well-being through a boundary fit microintervention - Nicolas Mueller; Larissa Haerdter; Margaretha Scholz; Julia Steinke; Verena C. Haun; Regina Kempen (Journal of Occupational and Organizational Psychology, 2025)
This study examines the effectiveness of a microintervention targeting the alignment between employees' preferred and enacted boundaries separating work and nonwork roles (i.e., boundary fit). Drawing on boundary fit theory and the action regulation at the work–family interface model, we developed a self-guided boundary fit microintervention incorporating education, goal-setting, and self-reflection components. Based on a randomized controlled trial, we compared an experimental group with two control groups. We assessed changes in perceived boundary fit, work–nonwork balance satisfaction, and subjective well-being across three waves—pre-intervention (T1), post-intervention (T2), and follow-up (T3)—with two-week intervals between assessments (NT1–T20.167em=0.167em90; NT1–T2–T30.167em=0.167em75). Participants in the experimental group exhibited greater increases in these outcomes than both control groups. Mediation analyses revealed that increases in perceived boundary fit mediated the intervention's effects on work–nonwork balance satisfaction and subjective well-being. Although the findings' generalizability may be constrained by the sample—comprising predominantly women and participants without caregiving responsibilities—the study contributes to the boundary management literature by demonstrating the effectiveness of a time-efficient intervention and illuminating its underlying mechanisms.
Keywords: 650; action regulation; boundary fit; boundary management; intervention study; randomized controlled trial; subjective well-being; work–nonwork balance